The role of host soluble inflammatory mediators induced by the BCG vaccine for the initiation of in vitro monocyte apoptosis in healthy Brazilian volunteers. Issue 1 (December 2015) - Lima, Jessica; Siqueira, Mariana; Pedro, Thaíze; Ponte, Carlos; Peres, Leandro; Marinho, Suelen; Castello-Branco, Luíz; Antas, Paulo
Abstract Background Tuberculosis (TB) is the second greatest killer worldwide that is caused by a single infectious agent. For its control, studies of TB vaccines are needed. Since Bacillus Calmette-Guerin (BCG) is the only vaccine against TB currently in use, studies addressing the protective role of BCG in the context of inducible inflammatory mediators are urgently required. Methods In this study, groups of HIV-negative adult healthy donors (HD;n = 42) and neonates (UV;n = 18) have been voluntarily enrolled, and BCG Moreau strain was used for the in vitro mononuclear cell infections for an initial period of 48 h. Subsequently, harvested conditioned medium (CM) was added to autologous resting cells for an additional 24, 48, and 120 h, and Annexin V, in conjunction with a vital dye, was then used for apoptosis detection. CM was also assayed for nitric oxide (NO), prostaglandin E2 (PGE2 ), leukotriene B4 (LTB4 ), interferon (IFN)-β, and transforming growth factor (TGF)-β1 levels. Thep values were set up for any differences between two groups of individuals using Student'st -test and considered significant when ≤ 0.05. Results At 120 h, CM induced the highest apoptosis levels in both group studied, but necrosis was high in UV group only (p -value < 0.05). NO was released equally during BCG infection in both groups, but higher levels were found in HD when compared with UV group (p -value < 0.05). Overall, BCG Moreau triggered high PGE2, LTB4 and IFN-β productions in macrophages from the UV group (p -value ≤ 0.05), whereas the prostanoid PGE2 and TGF-β1 had an opposite pattern in the HD group. Conclusions This study uncovers critical roles for endogenous compounds in the instruction of host macrophage cell death patterns. Understanding the regulation of human immune responses is critical for vaccine development and the treatment of infectious diseases. These findings shed new light on the potential condition for a booster immunization in individuals already vaccinated with BCG for TB protection, and further studies are warranted.